2016
DOI: 10.1103/physrevb.93.094418
|View full text |Cite
|
Sign up to set email alerts
|

Curvature and torsion effects in spin-current driven domain wall motion

Abstract: The domain wall motion along a helix-shaped nanowire is studied for the case of spin-current driving via Bazaliy-Zhang-Li mechanism. The analysis is based on collective variable approach. Two new effects are ascertained: (i) the curvature results in appearance of the Walker limit for a uniaxial wire, (ii) the torsion results in effective shift of the nonadiabatic spin torque parameter β. The latter effect changes considerably the domain wall velocity and can result in negative domain wall mobility. This effect… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 41 publications
3
45
0
Order By: Relevance
“…It is worth noting that there is a dependence of λ on θ and ϕ, coming from the fact that the demagnetizing field of a curved wire depends on the direction in which the magnetization field is pointing to [26]. However, because of the considered dimensions, this difference is small, and we will adopt λ = 1/4 to describe magnetostatic contributions to the energy [8,17,20]. In terms of the adopted parametrization, the exchange energy density is given by [17,27] …”
Section: Theoretical Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…It is worth noting that there is a dependence of λ on θ and ϕ, coming from the fact that the demagnetizing field of a curved wire depends on the direction in which the magnetization field is pointing to [26]. However, because of the considered dimensions, this difference is small, and we will adopt λ = 1/4 to describe magnetostatic contributions to the energy [8,17,20]. In terms of the adopted parametrization, the exchange energy density is given by [17,27] …”
Section: Theoretical Modelmentioning
confidence: 99%
“…It was also shown that the spin-current driven DW motion is strongly dependent on curvature and torsion [20]. In this case, the curvature results in the existence of a Walker limit for uniaxial wire, and the torsion induces an effective shift of the nonadiabatic spin torque parameter [20]. The direction of motion of a DW along a helical wire under the action of a Rashba spin orbit torque depends on the helix chirality and wall charge in such way that DWs can be moved only under the action of Rashba and geometrical effects [21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We refer to these as vortex states. Unlike the case of the helicoid ribbon, φ ≡ ±π/2 is not a solution of (23). Numerically, we find two further solutions of the Euler-Lagrange equation, denoted φ rib + (χ) and φ rib − (χ) ≡ φ rib + (χ) + π, which we call ribbon states.…”
Section: (A) (B)mentioning
confidence: 96%
“…field-like torques [18] and anti-damping torques [23]. In the particular case of a helical nanowire, torsion can produce negative domain wall mobility [18,23], while curvature can produce a shift in the Walker breakdown [23].…”
Section: Introductionmentioning
confidence: 99%